A motivação no trabalho como antecedente da satisfação, do comprometimento e do desempenho: um estudo em um hospital público - Cunha, Luciane da Veiga (2013)
The study of work motivation receives considerable interest in the international literature, probably, due to its close relationship with the individual and organizational performance (TAMAYO; PASCHOAL, 2003), while the national studies are few. According to Godoi (2002), studies of human motivation at work are stalled due to the complexity of the approaches that make up the psychology of the individual and also to the insufficient depth critical analysis of ideas to behaviorists authors still present in the organizational studies on motivation. This issue coupled with the need of hospital organizations, one of the most complex not only by the nobility of its mission, but especially by presenting a multidisciplinary team to assist patients in a preventive, curative and rehabilitating manner (AZEVEDO, 1993), raises the question: "What is the level of the motivation in a public hospital organization, and what is its influence on other organizational behaviors?" Based on the model adapted from Vandenabeele (2009), originally created for the public sector, and the scale of work motivation proposed by Gagné et al., (2010) according to the multidimensional concept of motivation postulated in the Self-Determination Theory (SDT, DECI; RYAN, 1985), this study is characterized as a quantitative, descriptive research with four scales that measured the motivation, the satisfaction, the commitment and the performance of the employees of the Hospital Universitário de Santa Maria (HUSM). The averages of motivation found this research are, in the large majority, above the midpoint of the scale and indicate the predominance of the identified motivation (GAGNÉ et al., 2010), which is positive, since the identified motivation produces better performance on tasks that require discipline and determination (KOESTNER; LOSIER, 2002). Sociodemographic variables (gender, age, education, time on the job and income) and occupational variables (employment link, level of function and management to which the employees are subordinated) influenced, significantly, the averages of the identified motivation. The analysis of the regression found that the work motivation is an antecedent of the satisfaction, with a moderate degree of dependence (R2=27.6%) and is also an antecedent of the three dimensions of commitment, with a very small and a small dependence (R2=3.2%) for affectionate commitment, (R2=10.5% for normative commitment and R2=7.5% for instrumental commitment). For the performance, the motivation is an antecedent with a very low degree of dependence (R2=3.4%), contrary to the normally expected. It was also verified that the kind of the motivation influences, differently, on the performance, on the satisfaction and on the organizational commitment, reinforcing the importance of studying the motivation in a multidimensional way, as emphasized Gagné e Deci (2005).